An Analysis of the Effectiveness of Information and Communication Technology Technologies in Providing Customer Feedback to Enhance B2C Value Co-creation: A Focus on the Tourism Industry - Mgoduka, Siyasanga; Kaseeram, I.; Heeralal, S. (International Review of Management and Marketing, 2024)
Recent tourism research has shown a move towards the perspective on ‘value-in-use’ or ‘value-in-context’ that customers can co-create value through interactions with tourism organizations. As value is co-created through an ongoing interactive learning process, customers are involved in every step of service creation, from jointly defining problems to collaboratively solving them, this is enabled through intense engagement and dialogue possibilities between customers and companies. This study aims to analyse the effectiveness of ICT technologies in providing customer feedback to enhance B2C value co-creation. Information and communication technology (ICT) competences have been deemed essential for the use and execution of digital solutions, including external relationship management, technical proficiency, and planning. The results from this current study indicated a strong positive relationship between customer feedback in a form of transparency and value co-creation. Moreover, this study found that ICT platforms such as social media and emails are the fastest way to exchange digital messages over the internet and are thought to be the most recent, dependable method in marketing and electronic commerce. Furthermore, this study revealed a strong positive relationship between customer feedback in a form of a dialogue and its contribution to value co-creation. Therefore, this study concludes that firms should engage consumers in a dialogue regarding the service provision through the use of ICT technologies in order to enhance value co-creation.